Deformation Analysis of 2012 Mw8.6 Indian Ocean Earthquake Based on GPS Data in Preseismic, Coseismic, and Postseismic Phases - Marzuki Marzuki; Zul Ikram; Vira Friska (Postgraduate, University of Mataram, 2022)
The earthquake was one of the biggest natural disasters in Sumatra and dramatically affected this region and the surrounding area. Determination of surface deformation due to the earthquake is essential for disaster mitigation. The Global Navigation Satellite System (GNSS) is a commonly used method for determining surface deformation due to earthquakes. This study analyzes surface deformation during the preseismic, coseismic, and postseismic phases due to the 2012 Mw8.6 Indian Ocean earthquake. The study used Global Positioning System (GPS) data from the Sumatran GPS Array (SuGAr) network. The most significant horizontal deformation was observed at the LEWK station, which was 280.554 mm towards the northeast and experienced a subsidence of 40.830 mm in vertical deformation. Horizontal deformation is still felt by 22.453 mm to the northeast and vertical deformation of 8.810 mm (uplift) at stations that are farther (580 km) from the earthquake's epicenter. However, in the observation period of 60 days (postseismic phase), stations closer to the epicenter are still experiencing a postseismic phase. In contrast, stations far from the epicenter show that the postseismic phase is almost complete. In the preseismic phase, all stations experience almost the same horizontal deformation, ranging from 2.210 mm-3.639 mm, but with a different direction of movement, which may be caused by previous intense earthquake activity, which is still releasing energy (postseismic phase). On the other hand, the vertical deformation during the preseismic phase generally experiences an uplift except at the LEWK station. The results of this study can be additional information for earthquake mitigation in the Sumatra region